Description of two new species of Nemoleon Navás, 1909 (Neuroptera, Myrmeleontidae) from India - Suryanarayanan, Thangalazhi Balakrishnan; Ábrahám, Levente; Bijoy, Chenthamarakshan (Zootaxa, 2023)
The Nemoleontid genus, Nemoleon Navás, 1909 from the Oriental realm, with two new species namely Nemoleon ghoshi sp. nov. and Nemoleon madayiensis sp. nov. are described from Kerala, India. Also, a species key of Nemoleon from India based on the adult characters is provided, and compered to African species.